Undiagnosed chronic obstructive pulmonary disease in patients admitted to an acute assessment unit - Karin D. Eikhof; Kristine R. Olsen; N. C. H. Wrengler; Carl Nielsen; Uffe Boedtger; Ingrid L. Titlestad; Ulla M. Weinreich (European Clinical Respiratory Journal, 2017)
Introduction: Chronic obstructive pulmonary disease (COPD) is very prevalent worldwide, yet underdiagnosed Aim: This study investigates feasibility of performing spirometry in patients in need of acute hospital admission as well as the prevalence of undiagnosed COPD in the same cohort. Methods: During a two-week period, all patients admitted to three large acute assessment units were evaluated. Patients ≥ 18 years, able to perform spirometry, with no surgery to the thorax or abdomen within the last weeks and no known COPD was included. Patients with FEV1/FEV6 ≤ 0.7 or FEV1 < 80% or FEV6 < 80% were offered follow-up visit after 6 weeks. Results: Of the 1145 admitted patients, 46% were eligible: 28% of those had an abnormal spirometry. The offered follow-up visit was attended by 51% and in this group 17% were diagnosed with lung disease. COPD was the most prevalent diagnosis (73%), and 2/3 was in GOLD group A. In total, 75% of the patients with airflow obstruction at the initial examination remained obstructive. Conclusion: Performing spirometry in patients in need of acute hospital admission is feasible, abnormal findings are common, and COPD is the most prevalent diagnosis.